Fractionation of stable oxygen and clumped isotopes during acid digestion of calcite in the presence of an external direct current electric field. (23rd September 2020) - Banerjee, Sanchita; Ghosh, Prosenjit; Pramanik, Chirantan; Reddy B, Subba
Abstract : Rationale: Phosphoric acid digestion of carbonate generates CO2 for stable oxygen and clumped isotope analysis using a gas source isotope ratio mass spectrometer. The initial step of the digestion reaction is protonation of calcite while the product CO2 equilibrates with the system allowing further exchange of isotopes to various extents depending on the nature of the acid digestion methods. An external electric field is introduced in the break seal method to demonstrate the role of the protonation reaction and the post‐digestion isotopic exchanges in the final isotopic composition of product CO2 . Methods: An acid digestion experiment following the break seal method was conducted at a constant temperature of 25 ± 0.5°C in the presence of a uniform external electric field of 0.5 kV/cm within a specially fabricated corona chamber. Replicate samples of a calcite powder of a reference standard (MAR J1) were reacted for 24 h in the presence and absence of an external electric field for varying exposure times (6 to 24 h) and the evolved CO2 was analyzed using a dual‐inlet MAT 253 isotope ratio mass spectrometer. Results: The CO2 yield from the phosphoric acid digestion of MAR J1 calcite was 20% lower during the reaction in presence of an electric field for an exposure time of 24 h, while the corresponding δ 18 O value and Δ47 composition were 0.3‰ and 0.1‰ less, respectively, than without any electric field. Conclusions: We documented the systematic control of oxygen and clumped isotope ratios in CO2 evolved from the carbonate acid digestion reaction with varying exposure time to the external electric field. We provide a new method involving use of an external electric field to manipulate the isotopic fractionation during the acid digestion reaction of calcite. The experimental observation enabled theoretical understanding of the reaction mechanism of carbonate with phosphoric acid which will be useful for stable and clumped isotope studies.